TI_GERICHTE 52.2021.295 vom 2. Juni 2021 , Divieto di fare uso sul territorio svizzero di una licenza di condurre straniera - TI Tribunale d'appello (2021)
Divieto di fare uso sul territorio svizzero di una licenza di condurre straniera